2023
DOI: 10.1108/jfra-06-2022-0237
|View full text |Cite
|
Sign up to set email alerts
|

IFRS 9, earnings management and capital management by European banks

Mohammadmahdi Norouzpour,
Egor Nikulin,
Jeff Downing

Abstract: Purpose The purpose of this paper is to compare earnings management (EM) and capital management (CM) by European banks before and after the adoption of IFRS 9. After IFRS 9, banks have more discretion in recognizing loan-loss provisions than before IFRS 9. Hence, after IFRS 9, banks could use EM and CM to a greater extent. Design/methodology/approach This paper analyzes a sample of European banks and uses regression analysis. First, this paper examines whether EM and CM changed after IFRS 9 was adopted. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Firstly, we augment the debate on bank LC by focusing on the relevance of accounting standards. This contrasts with related prior research which focuses on the impact of IFRS-9 on other financial metrices such as provisions, risk-taking, credit or even capital management (Kim et al, 2020;Lopez-Espinosa et al, 2021;Abuaddous, 2023;Kyiu and Tawiah, 2023;Salazar et al, 2023;Norouzpour et al, 2023). By integrating both asset-and liability-sides balance sheet items in a single measure, we provide a more comprehensive assessment of the impact of IFRS-9, an aspect that has not been adequately addressed earlier.…”
Section: Prior Evidencementioning
confidence: 92%
“…Firstly, we augment the debate on bank LC by focusing on the relevance of accounting standards. This contrasts with related prior research which focuses on the impact of IFRS-9 on other financial metrices such as provisions, risk-taking, credit or even capital management (Kim et al, 2020;Lopez-Espinosa et al, 2021;Abuaddous, 2023;Kyiu and Tawiah, 2023;Salazar et al, 2023;Norouzpour et al, 2023). By integrating both asset-and liability-sides balance sheet items in a single measure, we provide a more comprehensive assessment of the impact of IFRS-9, an aspect that has not been adequately addressed earlier.…”
Section: Prior Evidencementioning
confidence: 92%
“…Therefore, standard-setters' concerns might not be safeguarded, as the dynamic provisions present in this new model can potentially promote earnings management, impairing the transparency of financial statements (FASB-IASB 2009). Studies have shown mixed results regarding the impact of IFRS 9 on earnings management, with some indicating an increase in such practices, especially in less regulated environments (Nnadi et al 2023;Norouzpour et al 2023).…”
Section: Impact Of Dynamic Models On Economic Cycles Managementmentioning
confidence: 99%